Implementation quality of family literacy programmes: a review of literature. Issue 1 (25th September 2016) - de la Rie, S.; van Steensel, R.C.M.; van Gelderen, A.J.S.
Abstract : Raising the literacy levels of young children is a major concern in many countries for which various programmes have been suggested. One of these is family literacy programmes. In previous meta‐analyses wide variability in effects has been found and it has been suggested that this is partly caused by variability in implementation quality. This review aims to look at the implementation quality of family literacy programmes and its relationship with programme effectiveness. A search in relevant databases resulted in 46 studies. We found substantial, but variable information on implementation quality. Almost all studies provided information on parents' quantitative engagement in programmes, but fewer studies reported about characteristics of parent training, quality of engagement and transfer to daily life. Overall, the included studies that did provide information showed frequent use of intervention strategies and degree of participation was generally high. Parents increased their use of the learned techniques and engaged in more literacy activities outside programme time. However, few of the included studies analysed the relationship between implementation quality and programme effects and these studies provided mixed results, making it difficult to draw conclusions. Of critical note is the poor quality of the selected studies. Many had serious methodological flaws. Some of the measures used are not necessarily reliable indicators of implementation quality and results were at times presented with little precision. More robust evaluations of the effects of implementation quality are therefore needed.